Clinical presentation and surgical outcome among patients having single and multiple gallstones: a prospective study - Baghel, Aditya Singh; Anand, Krishnanand; Gupta, Saumya (International Surgery Journal, 2022)
Background: Outcome of laparoscopic cholecystectomy is determined by an array of factors including patient & gallstone-related variables. Number of gallstones influences pathophysiology of disease thereby influencing outcome of surgery. This study was aimed at investigating clinical, haematological, radiological features and surgical outcomes among patients having single and multiple gallstones. Methods: Single centre, hospital-based, prospective, observational study involving 60 patients undergoing LC. Data pertaining to clinical, hematological, radiological variables and surgical outcomes were collected and analysed. Results: Mean duration of symptoms (m/c- pain) was significantly shorter among participants having multiple gallstones (p=0.034). There was no statistically significant difference among participants having single and multiple stones regarding any of clinical signs and symptoms (p>0.05). Mean GB wall thickness among patients having single and multiple gallstones was 3.27 mm and 4.18 mm (p=0.038). Difference in proportion of patients having pericholecystic collections was statistically significant (p=0.019). Mean duration of surgery among participants with single and multiple stones was 57 minutes and 71 minutes, respectively (p=0.012). On intraoperative examination, adhesion was noted in 20% of participants with single stone and 35% of participants in multiple stones group (p=0.029). Conversion rate to OC was 12% in multiple stones group and only 3.4% of participants with single stone (p=0.028). Adjusted odds ratio for conversion to OC was 3.39 (95% CI 1.98-7.89) for patients having multiple gallstones. Conclusions: Although patients having single and multiple gallstones have similar clinical features, findings of ultrasonography and surgical outcomes may differ significantly.